The effects of attitudes towards statistics, perceived ability, learning practices and teaching practices on students’ performance in statistics: a review - Mahmud, Zamalia; Ismail, Nor Zatul-Iffa; Abu Kassim, Noor Lide; Zainol, Mohammad Said (IIUM Press, International Islamic University Malaysia, 2018)
This paper reviews the literature related to the teaching and learning of statistics and highlights the following variables affecting students’ performance in statistics: students’ attitudes towards statistics, students’ perceived ability in statistics, instructors’ teaching practices and students’ learning practices. These variables have been chosen as these variables come from the self (student and teacher) where if self is well directed, teaching and learning becomes less complex and understanding will easily be established. Seeking knowledge has been greatly emphasized in Islam. The teaching and learning of statistics is becoming an increasingly important issue in statistical education. One pressing issue is how to continuously improve the teaching and learning of statistics at the tertiary level. Given its importance for the development of statistical literacy, statistical education researchers have attempted to investigate factors that relate to students’ learning outcomes in statistics and these researches have shown that a number of factors are indeed associated with student performance in statistics. The Prophet Muhammad (S.A.W) said: “The seeking of knowledge is obligatory for every Muslim”.2 And the civilization of Muslims has been based on lslam's emphasis on teaching and learning. © 2018, International Islamic University Malaysia. All rights reserved.